Legalitas Tindakan Penagihan dan Eksekusi Jaminan Fidusia oleh Debt Collector dalam Perspektif Perlindungan Hukum Kreditur - Bagas Agdi Pratama; Abraham Ferry Rosando (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
From the perspective of creditor legal protection in Indonesia, this paper examines the legitimacy of debt collection and the enforcement of fiduciary guarantees by debt collectors. By enabling ownership of movable property through fiduciary-backed loan schemes, the financial industry plays a vital role in the economy. However, debtor default often leads to law enforcement and collection actions, in which debt collectors play a crucial and often controversial role. This paper examines recent regulations, such as Financial Services Authority Regulation No. 22 of 2023, Financial Services Authority Circular Letter No. 19/SEOJK.06/2023, and the implications of Constitutional Court Decisions No. 18/PUU-XVII/2019, No. 2/PUU-XIX/2021, and No. 57/PUU-XIX/2021. The research method used is normative legal research, utilizing legal and intellectual perspectives. The findings demonstrate that debt collectors can legally carry out fiduciary guarantee execution and debt collection as long as they follow protocols and are accountable to the financing organizations who employ them. The decisions of the Constitutional Court do not eliminate the creditor's executive rights; Rather, they make clear the prerequisites for their execution, which include the debtor's voluntary surrender of the collateral item and acknowledgment of default, or a court order. In order to preserve investment certainty and the stability of the financial industry, which in turn promotes economic growth, creditors must have legal protection